2013
DOI: 10.1111/cns.12163
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Suppresses Malignant Glioma Cells Growth and Induces Apoptosis by Inhibition of SHH/GLI1 Signaling Pathway in Vitro and Vivo

Abstract: This study shows that curcumin holds a great promise for SHH/GLI1 targeted therapy against gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 40 publications
(50 reference statements)
3
60
0
1
Order By: Relevance
“…[46][47][48] Previous studies found 49,50 that the inhibitory mechanism of p53 that relied on NF-κB existed in the kidney cancer cells. Quinacrine inhibited NF-κB and activated tumor suppressors of p53 simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] Previous studies found 49,50 that the inhibitory mechanism of p53 that relied on NF-κB existed in the kidney cancer cells. Quinacrine inhibited NF-κB and activated tumor suppressors of p53 simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…13,17 Briefly, the tumor tissues were deparaffinaged, rehydrated, treated with 0.3% hydrogen peroxide, and processed with antigen retrieval using heat induction for about 10 minutes. Samples were stained with anti-E-cadherin antibody (1:200, Proteintech) and anti-Vimentin antibody (1:200, Cell Signaling Technology).…”
Section: Immunohistochemistry (Ihc) Assaymentioning
confidence: 99%
“…13 Then we used Western Blot to test the EMT markers and the Hedgehog signaling pathway, which was reported to be the target signaling pathway of Curcumin. We chose 96 hours as a time period after g-irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Various concentrations of β-elemene (Dalian Jingang Pharmaceutical Co. China) were used for 20h.Then 5 mg/ml MTT (Sigma-Aldrich, USA) was added to each well for another 4h as reported previously (Du WZ et al, 2013). The amount of formazan was assessed by measuring the absorbance using TECAN microplate reader at 490nm.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…Cells were cultured for 12 days with complete medium. Then the colonies obtained were washed with PBS and fix in 10% formalin for 10min at room temperature (Du et al, 2013). Samples were stained with Giemsa stain and the number of colonies with more than 50 cells was counted.…”
Section: Cell Proliferation Assay and Colony Formation Assaymentioning
confidence: 99%